Model celovite obravnave funkcionalno degradiranih območij kot podpora trajnostnemu prostorskemu in razvojnemu načrtovanju v Sloveniji - Lampič, Barbara (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
This paper investigates the characteristics of functionally derelict areas in Slovenia, criteria for their identification, typology and arguments for further monitoring, and regular updating of this new spatial and data layer. Both specifying the precise location and knowledge of characteristics of derelict areas, i.e. brownfields, are an important step towards sustainable planning and placement of activities. In 2017, we recorded 1081 functionally derelict areas in Slovenia in a total area of 3423 ha, with a prevalence of areas of industrial activities.
Keywords: degradacija; environmental protection; natural environment; ogrožanje; okolje; onesnaževanje; prostorsko planiranje; regionalni razvoj; Slovenia; Slovenija; spatial planning; sustainable development; trajnostni razvoj; varstvo okolja